PENGEMBANGAN MEDIA PAKAKI (PAPAN TEKA-TEKI) UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN IPAS SISWA KELAS IV SDN JAYAMULYA 01 - Munawaroh, Chaflatun; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to increase the motivation to learn science science of grade IV students of SDN Jayamulya 01 in the development of Pakaki media (Puzzle Board). This study uses a type of RnD research with an ADDIE development model. The validity test was carried out by validators who produced 94% for the validation of material experts, 82% for the validation of linguists, and 96% for the validation of media experts. With all three validator scores yielding an average of 90.6% which indicates the category is very valid to be tested. The results of the teacher's response of 96% prove that the media is very good and practical to use. The results of individual trials produced 97.6%, small group tests 95% and field trials 94%, proving that the media is very good. The results of the effectiveness of learning motivation produced an average percentage of 94.28% which showed the category was very effective. Based on the results of the study, it can be concluded that Pakaki (Puzzle Board) media can increase students' learning motivation.